The ghost mammals from Mexico and their implications - Monroy-Gamboa, Alina Gabriela (THERYA, 2021)
The species records are key to determine their distribution. In México, there are records located up to more 200 km outside the known range of Ateles geoffroyi, Cryptotis mayensis, Pteronotus davyi and Tlacuatzin sinaloae. Other species were captured in their type locality but have not been recorded again over up to 100 years: Dipodomys gravipes, Oryzomys peninsulae, Peromyscus mekisturus, P. pembertoni, Sorex sclateri, S. stizodon, Tylomys bullaris and T. tumbalensis. This study analyzes these mammalian species records, their information gaps related with their known range, and discusses the likely implications for conservation. A survey of the literature and databases of scientific collections available on the Internet were conducted. A geographic information system was used for the spatial analysis of the records obtained. Records outside the limit of the known range of these species are due to misidentification of specimens, accidental introduction and lack of field corroboration. Some of the species captured only in their type locality can be deemed extinct while others require field and laboratory work. Geographic records of the species are valuable inputs to define the distribution range of species and advance our current knowledge about the Mexican. The use of records with errors or that should no longer be considered have an impact on the risk categorization of species and the development of conservation strategies.